Cylindroconidiis aquaticus gen. et sp. nov., a new lineage of aquatic hyphomycetes in sclerococcaceae (eurotiomycetes) - Xian Dong Yu (2018)
© 2018 Magnolia Press. During our ongoing investigations of freshwater fungi in Thailand, Cylindroconidiis aquaticus gen. et sp. nov. is described in the family Sclerococcaceae (Eurotiomycetes), based on morphological characters and phylogenetic analyses of LSU, SSU and ITS sequence data. Its closest relatives are Rhopalophora species and Fusichalara minuta. The new genus is characterized by mononematous, unbranched conidiophores, polyblastic, terminal or intercalary conidiogenous cells, and ellipsoidal to cylindrical, 1-septate conidia. It is the first report of freshwater fungi encountered in Sclerococcaceae.